Local Electricity Distribution in Italy: Comparative Efficiency Analysis and Methodological Cross-Checking - Gian Carlo Scarsi (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper analyses technical efficiency of local electricity distribution in Italy (1994, 1996) by using both econometric (deterministic frontier, stochastic frontier) and linear programming (Data Envelopment Analysis) tools. Cross-sectional data were examined with respect to:(a) ENEL - the Italian electricity monopolist;(b) municipal authorities (MUNIs), i.e. town-based electric utilities which sometimes hold franchises for electricity distribution within city limits.Estimation results highlighted non-exhaustion of scale economies at sample-mean values. Pooled ENEL-MUNI analysis failed to spot any systematic superiority of ENEL's units over municipalities. One-to-one comparisons confirmed that the outcomes were mixed, with ENEL's local branches outperforming MUNIs in metropolitan and (sometimes) rural areas, and MUNIs faring better in medium-sized, Po Valley towns (Northern Italy). This suggests that a case-by-case approach should be adopted by Italy's regulatory and governmental authorities when dealing with the territorial reform of electricity distribution. Similarly, any ownership transfers and/or mergers involving ENEL's units and MUNIs should depend on the varied efficiency records which were detected according to different regional and economic scenarios.
Keywords: L94; L98; L51; 330; Electricity; Government Policy; Efficiency; Elektrizitätswirtschaft; Kommunale Energiewirtschaft; Technische Effizienz; Italien